Music teachers in (self)formation movements: thinking about formation “among us” (Orfeu, 2025)
The music teacher formation has been the subject of significant research in Music Education, fostering theoretical advancement and the critical examination of specific aspects that interconnect music(s) and education(s). This study highlights the importance of understanding music teacher education through the lens of professional practice, with a focus on continuing education. Based on theoretical pathways linked to ongoing research (Schneider, 2023), this article proposes a reflection on the continuing education of music teachers from the perspective of (self)formation and the group as a formative device. The goal is to (re)think continuing education for music teaching professionals, emphasizing the potential of a formation "among us"—the self, the other, and the profession. In this approach, the formation "among us" is permeated by (self)formative experiences and group dynamics that create time and space for reflection and the (re)construction of the profession. Thus, this type of formation intertwines withthe university, the school, and the teachers themselves, reflecting the complex web that encompasses professional practice and music teaching.
Keywords: music education; music teacher formation; (Self)formation; group